Operational challenges in managing Isoniazid Preventive Therapy in child contacts: A high-burden setting perspective - van Wyk, Susan S; Reid, Anthony J; Mandalakas, Anna M; Enarson, Donald A; Beyers, Nulda; Morrison, Julie; Hesseling, Anneke C (BMC public health, 2011)
Background The study was conducted at a high TB-HIV burden primary health community clinic in Cape Town, South Africa. We describe the management of children under five years of age in household contact with a smear and/or culture-positive adult TB case. Methods This study was a record review of routinely-collected programme data. Results A total of 1094 adult TB case folders were reviewed. From all identified contacts, 149 children should have received IPT based on local guidelines; in only 2/149 IPT was initiated. Management of child contacts of sputum smear and/or culture-positive compared to sputum-negative TB patients were similar. Conclusions IPT delivery to children remains an operational challenge, especially in high TB-HIV burden communities. A tool to improve IPT management and targeting sputum smear and/or culture-positive TB child contacts may overcome some of these challenges and should be developed and piloted in such settings.